THE EFFECTIVENESS OF SMALL GROUP INTERACTION IN TEACHING READING COMPREHENSION - Siti Zakiah, Siti Zakiah; Aunurrahman; Hafiz, Maliqul (Melekliterasi Press, 2025)
This study evaluates how well the Small Group Interaction technique helps improve students’ reading comprehension. It uses a quantitative approach with a one-group pre-test and post-test design involving 33 grade VII B students from SMP Kemala Bhayangkari 1 Kubu Raya. Before applying the technique, a pre-test assessed students’ initial comprehension levels. Data focused on key reading skills like identifying main ideas and drawing conclusions. After analyzing the results with SPSS and Excel, the average score expand from 56. 66 in the pre-test to 80. 06 in the post-test. Statistical tests confirmed a significant improvement, leading to the acceptance of the hypothesis that the technique is effective for teaching reading comprehension. This method is recommended to enhance students’ reading skills and teachers’ teaching abilities Penelitian ini mengkaji seberapa efektif teknik Interaksi Kelompok Kecil dalam meningkatkan pemahaman membaca siswa. Metode yang digunakan adalah pendekatan kuantitatif dengan desain pre-test dan post-test satu kelompok yang melibatkan 33 siswa kelas VII B di SMP Kemala Bhayangkari 1 Kubu Raya. Sebelum menerapkan teknik tersebut, dilakukan pre-test untuk menilai tingkat pemahaman awal siswa. Data yang dianalisis lebih fokus pada keterampilan membaca utama seperti mengidentifikasi ide pokok dan menarik kesimpulan. Setelah menganalisis data menggunakan SPSS dan Excel, rata-rata skor meningkat dari 56,66 pada pre-test menjadi 80,06 pada post-test. Uji statistik membuktikan adanya peningkatan yang signifikan, yang mendukung penerimaan hipotesis bahwa teknik ini efektif dalam pengajaran pemahaman membaca. Metode ini direkomendasikan untuk meningkatkan keterampilan membaca siswa dan kemampuan mengajar para guru.